Characterisation of Streptomyces and their biocontrol activities against rice blast pathogen Pyricularia oryzae - Awla, Hayman Kaka Khan (2016)
Blast disease caused by the fungus Pyricularia oryzae is the most significant disease affecting rice cultivation and causing serious yield losses. To reduce the usage of chemicals, an alternative method for a sustainable control of the disease is necessary. Streptomyces have been known to produce antimicrobial compounds and are potential biocontrol agents. This study was carried out to isolate, identify and characterise Streptomyces isolates for in vitro screening against P. oryzae, to identify the antimicrobial compounds produced by selected Streptomyces isolates and their mechanisms of biocontrol, and to evaluate the efficacy of selected Streptomyces isolate against P. oryzae in the glasshouse. A total of 54 Streptomyces isolates were obtained from four sites in peninsula Malaysia including healthy and infected paddy fields. All the isolates were tested against P. oryzae by dual culture test on Potato Dextrose Agar (PDA) and 14 isolates showed growth inhibition of P. oryzae. The best two isolates with more than 80% Percentage of inhibition of radial growth (PIRG %) were selected for subsequent experiments. The isolates were identified as Streptomyces sp. based on the morphological, physiological and chemical characteristics and confirmed with 16S rRNA sequence analysis that was compared with related bacteria in GenBank database using MEGA 6.1. Isolates UPMRS4 (Streptomyces sp.) and UPM28 (Streptomyces zaomyceticus) were found to be the most effective Streptomyces against the pathogen with PIRG showing 98.3% and 86.3%, respectively. For extraction of bioactive compounds from UPMRS4, eight different solvents were used and the crude extract obtained from ethyl acetate was found to give the highest PIRG (88%). Bioactive volatile compounds from the ethyl acetate crude extract were identified using gas chromatography-mass spectrometry (GC-MS). Twenty-two volatile compounds were identified as major compounds in the isolated UPMRS4 that were possibly responsible for the antifungal activity. Four nonvolatile compounds from the same crude extract were identified using Liquid chromatography-Mass spectrometry MS (LC-MS MS) and the main compounds were N-Acetyl-D, L-phenylalanine, amicoumacin, fungichromin and rapamycin. For the glasshouse study, UPMRS4 was used as a seed coating for in vivo study with four treatments. The results showed significant disease suppression and enhancement of yield attributes compared to the untreated control. UPMRS4 isolate was able to reduce 80% of disease severity compared with other treatments and increase shoot height (15.13%), shoot dry weight (45.7%), leaf surface area (44.6%), root length (48.9%), root dry weight (63.2%), number of tillers (42.2%), yield (36.9%), panicle length (15.4%) and the number of spikelets/panicle (29.3%) compared to the control plants at three months after inoculation. Defense-related gene expression in rice leaf samples with seed coating application in both inoculated and un inoculated with P. oryzae was evaluated using quantitative real-time PCR Chitinase (Cht-l), ~-l, 3- glucanase, OsPRla, Oswrky45 and OsJAMYB genes were selected for the study during the three days. Rice plants inoculated with Streptomyces sp. UPMRS4 isolate demonstrated a higher abundance of defence gene expression compared with the nontreated controls. The outcomes indicate that UPMRS4 induced rice defence by enhancing the expression levels of OsPRla, Cht-L, Gnsl, Oswrky45 (SA) and OsJAMYB (JA).